Little Red Riding Hood - Lambert, Nat.; Butcher, Rosie (Melville, New York : Imagine That Group Ltd., 2018)
'Far, far away, in the African Savannah lived a little giraffe called Gregory who had no one to play with'. Join Gregory the little giraffe in the is funny story about friendship and accepting others.
Augmented Reality Book.
Read, Learn, and Play! With Augmented Reality. 4D Magic.
For ages 1-5 years.
Keywords: Readers -- Juvenile fiction; Basic English; Children's stories